PHYSICAL DEVELOPMENT OF CHILDREN SUFFERING FROM ALLERGIC RESPIRATORY DISEASES - Devorova Ma'rifat Bakiyevna; Ulugov Askar Ismatovich; Nazarkulov Madaminbek Abdunazar Ugli (Scholar Express Journals, 2023)
In all children suffering from respiratory allergies, specific allergic reactivity has increased. Along with this, it became possible to identify some aspects of changes in the reactivity of the body based on the clinical forms of respiratory allergies and the type of regional allergens. Children who have allergic rhino conjunctivitis (ARC) were found more susceptible to pollen allergens. In cases of house dust allergen, children with allergic respiratory obstructive bronchitis (AROB) were especially vulnerable. In children with asthma, the allergic reactivity of the body to the allergen from house dust were 2-5 times higher than other types of that, such as pollen dust and epidermal allergens. ergens from house dust mites was 2-5 times higher than to pollen and epide.
Keywords: Allergy; allergen; bronchial asthma